Activity Systems Analysis Methods - Yamagata-Lynch, Lisa C. author. aut Link
XVI, 148 p.
Keywords: Cultural Historical Activity Theory (CHAT) has its origins in Lev Vygotsky’s pioneering work in the 1920s. More recently, education scholars have used CHAT to study learning behavior through the creation of activity systems analysis. Activity Systems Analysis Methods brings the CHAT framework into clear practical focus to offer a non-dualistic perspective on contemporary learning process in context. By focusing especially on methodologies, and including numerous real-life examples, the book moves beyond the theoretical realm to provide readers with expert guidance in mapping and evaluating complex learning interactions in natural environments. This first-of-its kind volume: • Summarizes the theoretical development of CHAT and activity systems analysis. • Explains how researchers perform activity systems analysis, and ways it benefits educational research and practice. • Addresses challenges to the validity of activity systems analysis. • Provides detailed examples of activity systems analysis used toward various research goals. • Identifies methodological issues salient to designing and conducting CHAT-related studies in qualitative research. • Refers readers to additional resources on activity systems analysis theory, methods, and issues. Education researchers, particularly in instructional technology and design, learning sciences, and educational psychology, will find Activity Systems Analysis Methods an exciting resource for adding new relevance and value to their work.